Current evidence of climate‐driven colour change in insects and its impact on sexual signals - Md Tangigul Haque; Md Kawsar Khan; Marie E. Herberstein (Ecology and Evolution, 2024)
Abstract The colours of insects function in intraspecific communication such as sexual signalling, interspecific communication such as protection from predators, and in physiological processes, such as thermoregulation. The expression of melanin‐based colours is temperature‐dependent and thus likely to be impacted by a changing climate. However, it is unclear how climate change drives changes in body and wing colour may impact insect physiology and their interactions with conspecifics (e.g. mates) or heterospecific (e.g. predators or prey). The aim of this review is to synthesise the current knowledge of the consequences of climate‐driven colour change on insects. Here, we discuss the environmental factors that affect insect colours, and then we outline the adaptive mechanisms in terms of phenotypic plasticity and microevolutionary response. Throughout we discuss the impact of climate‐related colour change on insect physiology, and interactions with con‐and‐heterospecifics.